The role of public relations in educating the Palestinian public about the issue of prisoners under the occupation An applied study on the employees of the Ministry of Detainees and Ex-Prisoners Affairs - Al-Manama, Wael AbdulRazaq (ALBAHITH ALALAMI, 2022)
The issue of Palestinian prisoners inside the prisons of the Israeli occupation is considered a humanitarian issue par excellence، as it affects every Palestinian family as a result of the absence of a husband، wife or son. Almost no Palestinian house is vacant without one or more prisoners، and even women، children and the elderly are not spared from these arrests. The problem of the study was to identify the role of public relations in the Ministry of Detainees and Ex-Prisoners Affairs in educating the Palestinian public about the issue of prisoners، the nature of this role and the means used to bring support and solidarity with this important and sensitive issue through the applied study on the employees of the ministry. This study falls within the descriptive research، as the researcher used the survey method، and the practice methods survey was chosen through it.The ministry positively affects the public’s level of solidarity with the prisoners’ issue، and most respondents agree to a large extent that public relations have a role in decision- making in the ministry. Most of them agree that there are external factors that affect the work of public relations and its services. The researcher presented a set of recommendations، the most prominent of which was that the Public Relations Department should be interested in communicating with the internal and external audience of the ministry to draw up the department’s policy and plan.